Effect of Ethanolic Extract of Centella asiatica against Cortex Hypertrophy of Adrenal Gland Induced by Chronic Immobilization Stress in Rats - Hidayat, Achmad Nurul; Wasita,dr.,Ph.D, Brian -; Wiyono,dr.,M.Kes, Nanang - (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2015)
Background: Chronic stress affects the cortex changes such as hypertrophy which is caused by the physiology change of HPA (Hypothalamus-Pituitary-Adrenal) pathway. Pegagan extract contains beneficial compounds such as triterpenoid is known has antistress and antidepressant effect. This present study aims to investigate Ethanolic Extract of Centella asiatica (EEC) on cortex hyperthropy level induced by chronic immobiliztion stress in male rats. Methods: This study was laboratory experimental study with randomized post test only control group design. Paraffin blocks was processed from thirty Sprague Dawley male rats. They were previously subjected with chronic immobilization stress and then divided into 6 groups: control group given distilled water 1 mg/kg, stress + PGA (Pulvis Gummi Arabicum), stress + 150 mg/kg EEC, stress + 300 mg/kg EEC, stress + 600 mg/kg EEC and stress + fluoxetine 10 mg/kg. The treatments were performed for 21 consecutive days. Cortex hypertrophy was evaluated using ImageJ 1.48v software under light microscope from hematoxylin eosin staining. Statistic analysis was performed using Kruskall-Wallis test continued by Post Hoc Mann-Whitney Test with Bonferroni correction. Result: Kruskall-Wallis test result showed significant differences in six group with p= 0,007. Meanwhile, Mann Whitney test with Bonferroni correction did not show significant difference between stress + PGA group and other groups (p>0.05). The difference result only found between control group and stress + 300 mg/kg of EEC (p= 0,001). There were no significant difference between stress + fluoxetine 10 mg/kg and control group (p = 0,880). Conclusion: EEC was incapable to decrease cortex hypertrophy level of adrenal gland in Sprague Dawley male rats induced by chronic immobilization stress. Keywords: Centella asiatica, chronic immobilization stress, hypertrophy, adrenal glands.Â